Photoresist-less patterning of silicone substrates for thick film deposition. (April 2016) - Mergen, Silvana; Johnston, Benjamin; Cowan, Robert; Newbold, Carrie
Abstract: Traditionally, fabrication processes to produce microelectrode arrays for neural stimulating electrodes have employed photolithography and a photoresist layer to produce a pattern on a substrate which subsequently has a metal layer deposited. The deposited metal layer is then used to create stimulating electrodes that will ultimately be in close contact with neural tissue. While the process enables accurate fabrication at a reasonable cost, the use of photoresist in the process presents a number of issues. Photoresist is a contamination risk with the potential for chemicals to be absorbed into the silicone, which will then subsequently be in close proximity to neural structures, introducing a risk of toxicity. In addition, due to the use of flexible substrates such as silicone elastomer, patterning of films greater than 1 μm thick can be difficult. Whilst an obvious solution would be to avoid using photoresist in the fabrication process, few alternatives have been systematically investigated. We investigated use of shadow masks fabricated from glass, brass and silicone elastomer, and exploitation of the natural tackiness of the silicone substrate for mask adhesion. All three mask materials attached well to silicone, but each presented differing degrees of difficulty during alignment and mask removal. Subsequently, thin gold films (∼20 nm) and thick platinum films (∼8 μm) were deposited on the silicone substrates using the shadow masks. We discuss the mask fabrication, pattern definition, the difficulties which arose, and the benefits of using shadow masks for the fabrication of medical devices.